Framing fan fiction : literary and social practices in fan fiction communities - Busse, Kristina, 1967- (University Of Iowa Press, 2017)
"Gathering some of Kristina Busse's essential essays on fan fiction together with new work, Framing Fan Fiction argues that understanding media fandom requires combining literary theory with cultural studies because fan artifacts are both artistic works and cultural documents. Drawing examples from a multitude of fan communities and texts, Busse frames fan fiction in three key ways: as individual and collective erotic engagement; as a shared interpretive practice in which tropes constitute shared creative markers and illustrate the complexity of fan creations; and as a point of contention around which community conflicts over ethics play out. Moving between close readings of individual texts and fannish tropes on the one hand, and the highly intertextual embeddedness of these communal creations on the other, the book demonstrates that fan fiction is simultaneously a literary and a social practice. Framing Fan Fiction deploys personal history and the interpretations of specific stories to contextualize fan fiction culture and its particular forms of intertextuality and performativity. In doing so, it highlights the way fans use fan fiction's reimagining of the source material to explore issues of identities and peformativities, gender and sexualities, within a community of like-minded people. In contrast to the celebration of originality in many other areas of artistic endeavor, fan fiction celebrates repetition, especially the collective creation and circulation of tropes. An essential resource for scholars, Framing Fan Fiction is also an ideal starting point for those new to the study of fan fiction and its communities of writers"--